PENGARUH KEPERCAYAAN PELANGGAN DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN HIKECY KERUPUK SINGKONG PADA GALLERY HIKECY SAWAHLUNTO - Fhadell Trio Putra; Febsri Susanti (JURNAL PUNDI, 2023)
Micro, Small and Medium Enterprises (MSMEs) are a sector that is currently receiving special attention from the government. The existence of MSMEs cannot be eliminated or avoided in the development of a region. This study aims to determine the effect of customer trust and service quality on customer loyalty to Hikecy Cassava Crackers Products at the Hikecy Sawahlunto Gallery. Determination of the sample was carried out using a Stratified Random Sampling sample with a total of 98 customers as respondents. Data was collected by distributing questionnaires and then analyzed using descriptive statistics and Independent-Sample T-Test with SPSS version 16. The results of data analysis showed that Customer Trust, Tangibles, Reliability and Responsiveness were the main factors that determined the level of customer satisfaction. Meanwhile, Assurance and Emphaty have a less dominant contribution to customer loyalty.   Keywords        : Customer Trust, Tangibles, Reliability, Responsiveness, Assurance, Empathy and Customer Loyalty.